OPTIMIZING THE UTILIZATION OF SOCIAL MEDIA IN THE APPLICATION OF REGULATIONS AND PUBLIC AWARNESS CULTURE OF HYDROMETEOROGICAL DISASTERS IN SOUTH KALIMANTAN - FAHRIANOOR FAHRIANOOR; MUHAMMAD NIZAR HIDAYAT (CV KULTURA DIGITAL MEDIA, 2022)
South Kalimantan as a province prone to hydrometeorological disasters requires patterned settlement efforts. This solution requires systematic and patterned steps through the application of regulations and a culture of disaster awareness through socialization carried out by the government of Banjar Regency, Hulu Sungai Tengah Regency, and Tabalong Regency. The rise of social media used by the community can be a strategic choice in optimizing the dissemination of disaster information, especially floods. The method used in this study is interpretive qualitative, with a media ecology approach. The media ecology approach assumes that you can see people's behavior in capturing disaster information through social media. The theory used is New Media, and Phenomenology.